2020
DOI: 10.1051/e3sconf/202021709006
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of development cage fish farming

Abstract: The fishing industry has a special role in the development of the agricultural economy. Fish farming in cages is currently very important and is a promising and economically profitable form of growing marketable fish. The fishing industry has many advantages, such as beneficial effects on the health of the population, on the environment, and on the world’s economy. Activities carried out in the fish farming industry provide ample opportunities. These activities are the organization of fish farming clusters, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Choi et al [11] suggested that the increasing demand for fishery products, along with the identified limitations within the fishing industry, could be potentially addressed by the aquaculture industry by providing fish stocks. Sangirova et al [12] also supported that fish farming can reduce the cost of fish while maintaining the supply of many types of commercial fish. By 2030, it is projected that aquaculture will account for 60% of the production and 40% from fishing [13].…”
Section: Fish Farming and Modern Approachesmentioning
confidence: 99%
“…Choi et al [11] suggested that the increasing demand for fishery products, along with the identified limitations within the fishing industry, could be potentially addressed by the aquaculture industry by providing fish stocks. Sangirova et al [12] also supported that fish farming can reduce the cost of fish while maintaining the supply of many types of commercial fish. By 2030, it is projected that aquaculture will account for 60% of the production and 40% from fishing [13].…”
Section: Fish Farming and Modern Approachesmentioning
confidence: 99%
“…Based on the experiences made in the world and according to the statistics related to fish production in cage culture systems, it is very important. The most important advantages of culture of marine fish in cages are: the production of quality protein in the household consumption basket, the possibility of exporting products and earning foreign currency, the possibility of pushing fishing organizations towards sustainable marine aquaculture, the low fixed cost of fish farming in the sea compared to farming it in land systems, suitable conditions for culture of all kinds of species, job creation especially in deprived areas, and new and suitable job opportunities in coastal provinces, a very suitable and cost-effective method for cultivation and settling in deep water environments and using salty waters, the possibility of creating favorable rearing conditions without environmental stress, the possibility of moving in the presence of pollution, the need for small space and high production per unit area, attracting investors and national capitalists in the direction of a new activity, providing needed protein and fish meat, considering the increase in population and the limitation of fresh water resources, settlement and job creation in deprived areas and far from coastal areas, achieving mass production of valuable marine fish, multi-purpose use of water resources as recreation and fishing sport and rearing of various species (Sangirova et al, 2020).…”
Section: Aquatic Animals That Can Be Cultivated With the Help Of Uwsmentioning
confidence: 99%